The Effectiveness of Islamic Capital Market Schools in Enhancing Knowledge and Motivation towards Stock Investment in Generation Z - Hani Hasanah; Kurniawati, Ria (IJESS International Journal of Education and Social Science, 2024)
This research aims to determine the difference between before and after the implementation of the Shariah capital market school at Sheikh-Yusuf Islamic University Campus. This study is a quantitative research using the Mann-Whitney test as a differential test. Based on the research results, it is found that there is a difference in motivation and knowledge of the students at Sheikh-Yusuf Islamic University before and after the implementation of the Shariah capital market school activities.